Rola coachingu i mentoringu w procesie adaptacji nowego pracownika - Żarczyńska-Dobiesz, Agnieszka (The Role of Coaching and Mentoring in the Process of Adaptation of New Employees, 2008)
The article aims to present 'coaching' and 'mentoring/facilitation' as possible induction methods that can be applied in the process of accommodation of newly recruited Staff in work environment. The author presents the situation of a new employee at the time of his joining the organization. The author sets definitions and presents the essence of the discussed methods listing their benefits for both the organization and the newly recruited staff. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 274-282